Managing Rohis Extracurriculars to Internalize Love for God - Azahra Salsabilla salsabila (UIN Siber Syekh Nurjati Cirebon, 2026)
This study aims to describe the management of Islamic Spiritual (Rohis) extracurricular activities in internalizing the character of Love for God among students at SMPN 31 Bekasi City. The study is grounded in the need to manage school-based religious activities so that they do not merely become routine programs, but function as a directed process of character formation. This research employed a descriptive qualitative approach with a case study method. Data were collected through observation, semi-structured interviews, and documentation involving the Rohis advisor, student committee, and Rohis members. The data were analyzed using the Miles, Huberman, and Saldana interactive model consisting of data condensation, data display, and conclusion drawing. The analytical framework used George R. Terry's management functions, namely planning, organizing, actuating, and controlling, and Ratna Megawangi's character education theory, especially the pillar of love for God and all His creations. The findings show that Rohis planning is carried out through work programs based on worship habituation, Islamic studies, mentoring, and social activities. Organizing is implemented through role distribution among the advisor, student committee, and members. Implementation becomes a space for habituation, role modeling, and direct experience in developing gratitude, compassion, and loyalty. Supervision is conducted through attendance records, daily worship journals, activity evaluation, and direct guidance. This study confirms that the internalization of Love for God in Rohis does not occur automatically, but is shaped by systematic and sustainable extracurricular management.Keywords: extracurricular management, Rohis, George R. Terry, Ratna Megawangi, Love for God character